PEMBELAJARAN SCIENCE LITERACY DI MTSN 2 CIREBON MELALUI MODEL AUTHENTIC LITERACY: Investigation Of The Scientific Writing Program At Mtsn 2 Cirebon Through The Authentic Literacy Program (Jurnal TEKNODIK, 2024)
Students' literacy skills in Indonesia still need to be improved. This is also in line with the government's plans for the research school program. One school that has implemented a research school is MTsN 2 Cirebon. This research aims to identify the implementation of the research program and its impact on students' literacy skills. This research uses a mixed-method method with qualitative-quantitative analysis techniques. The results of this research are: In the research program at MTsN 2 Cirebon, learning was carried out using various methods, including using technology, providing case studies, and collaborating with supervising teachers and peers, and presenting the results of observations. Based on the program that has been undertaken, the impact of these literacy abilities on four variables, namely reading and writing literacy skills, knowledge about literacy, motivation in reading and writing, and reflecting on the results of experience and material in the writing and reading process, it can be said that students have the ability quite high for these indicators.
Keywords: literasi sains